PENGARUH KEPEMIMPINAN DAN PELAKSANAAN PRINSIP GOOD GOVERNANCE TERHADAP KINERJA PEGAWAI DINAS PERDAGANGAN KABUPATEN MAJALENGKA - Ratna Rainia; A Yunus; Diding Bajuri (DIALOGIKA, 2020)
The application of the principles of good governance in government agencies is considered necessary for research considering the importance of the level of achievement of the implementation of good governance and its effect on improving performance by maximizing the role of leadership in implementing the principles of implementing good governance. effectively and efficiently. The research method used is descriptive and verification methods carried out through data collection in the field. The sampling used in this research is proportional random sampling technique. The data analysis method in this research uses descriptive analysis and verification analysis which can assist in processing, analyzing and interpreting the data under study. The analysis technique used in this research is path analysis. The results showed that the leadership role, good government and performance in the Department of Trade and Industry in Majalengka Regency has been running quite well. The influence of leadership and good governance on employee performance. Based on the results of data processing using SPSS, it is obtained data which shows that partially leadership has a significant effect on employee performance, as well as good governance has a positive and significant effect on employee performance. The results of the research simultaneously prove that leadership and good governance have a positive and significant effect on employee performance